An evaluation of the consistency of the defensive and dynamic objectives of the Federal Reserve policy - Grossman, Leroy Jerome (London : Ann Abor, 1963)
The purpose of this study is to evaluate the defensive operations as the have been conducted since the Treasury - Federal Reserve Accord of march 1951.
Thesis submitted to the Faculty of the Graduate School of Vanderbilt University in partial fulfillment of the requirement for the degree of Doctor of Philosophy in Economics , June, 1963.
Includes bibliographical references.
osc 09/02/17
Loans
Keywords: Central Banking, Federal Reserve